Prolegómenos sobre o processo de transformação capitalista da actividade educativa nos níveis básico e secundário de escolaridade - Leopoldo Mesquita (Universidade do Minho, 2011)
This paper aims to expose the foundations of a suggested new field on educational research, whose object is the capitalist transformation (or capitalization) of the educational activity in the elementary and secondary levels, which is considered as the present dominant trend in educational policies all over the world. It is argued that such an educational change configures a classic process of capitalist transition whose nodal point is the transformation of school work. Under the slogan of "continuous improvement" of school results, it is intended to constitute the productivity of students work as the measure of the productivity of the teacher's work. In this context, a detailed study of the forms of capital valorization in the education industry is required. Occurring mainly within the public education systems, the current educational transformation involves deep changes both in state structures and in the relationships of educational production. The concepts of capitalizer state and for-capitalist forms of market are used to analyze these changes.